DNA damage induced by hydroquinone can be prevented by fungal detoxification - Pereira, Pedro (2022)
© 2014 The Authors. Published by Elsevier Ireland Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).